(untitled) (Italian Journal of Public Health, 2007)
Background: Worksite health promotion (WHP) addresses diverse individual and work-related health determinants. Thus, multiple, non-standardized interventions as well as company outcomes other than health have to be considered in WHP research. Methods: The article builds primarily on published research reviews in WHP and related fields. It discusses key practical and research challenges of the workplace setting. The evidence available on the effectiveness of WHP is summarised and conclusions are drawn for future WHP practice and research. Results: WHP research on health-oriented, behavioural interventions shows that the level of evidence ranges from suggestive to acceptable for key prevention areas such as physical activity, nutrition, fitness, smoking, alcohol and stress. Such interventions are effective if key conditions are met. Future research is needed on long-term effects, on multi-component programs and on programs, which address environmental determinants of health behaviour as well. Research on work-related determinants of health shows the economic and public health relevance of WHP interventions. Reviews of work-oriented, organisational interventions show that they produce a range of individual and organisational outcomes. However, due to the complexity of the organisational context, the generalisability and predictability of such outcomes remain limited. Conclusions: WHP research shows success factors of WHP and provides evidence of its effectiveness. In future, the evidence base should be expanded by developing adaptive, company-driven intervention approaches which allow for continuous optimisation of companies from a health perspective. Also, approaches for active dissemination of such a systemic-salutogenic occupational health management approach should be developed to increase the public health impact of WHP.